БАЛАНСИРОВКА ЭНЕРГЕТИЧЕСКИХ ХАРАКТЕРИСТИК СЕНСОРОВ В БЕСПРОВОДНЫХ СЕНСОРНЫХ СЕТЯХ - Осинский, Антон Константинович; Петрова, Валентина Николаевна (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2020)
Актуальность работы обусловлена все более широким распространением беспроводных сенсорных сетей и необходимостью продления срока их жизни, которая определяется в основном разрядом встроенного в сенсор источника питания. Целью работы является разработка метода балансировки энергетических характеристик сенсоров в беспроводной сети. Balancing the energy performance of sensors in wireless sensor networks The paper proposed a method of balancing the energy characteristics of sensors in wireless networks. The method is based on the use of energy in the radio range of sensors transmitting data. The currently inactive sensors can receive and detect data packets and use them to recharge the power supply. Energy efficiency is determined by the accuracy of matching the receiving antenna with the input circuit and the voltage drop across the rectifier module. The analysis of relative losses depending on the frequency for a typical antenna of the wireless range.